Wwox deletion leads to reduced GABA-ergic inhibitory interneuron numbers and activation of microglia and astrocytes in mouse hippocampus - Hussain, Tabish (2019)
The association of WW domain-containing oxidoreductase WWOX gene loss of function with central nervous system (CNS) related pathologies is well documented. These include spinocerebellar ataxia, epilepsy and mental retardation (SCAR12, OMIM: 614322) and early infantile epileptic encephalopathy (EIEE28, OMIM: 616211) syndromes. However, there is complete lack of understanding of the pathophysiological mechanisms at play. In this study, using a Wwox knockout (Wwox KO) mouse model (2 weeks old, both sexes) and stereological studies we observe that Wwox deletion leads to a significant reduction in the number of hippocampal GABA-ergic (γ-aminobutyric acid) interneurons. Wwox KO mice displayed significantly reduced numbers of calcium-binding protein parvalbumin (PV) and neuropeptide Y (NPY) expressing interneurons in different subfields of the hippocampus in comparison to Wwox wild-type (WT) mice. We also detected decreased levels of Glutamic Acid Decarboxylase protein isoforms GAD65/67 expression in Wwox null hippocampi suggesting lower levels of GABA synthesis. In addition, Wwox deficiency was associated with signs of neuroinflammation such as evidence of activated microglia, astrogliosis, and overexpression of inflammatory cytokines Tnf-a and Il6. We also performed comparative transcriptome-wide expression analyses of neural stem cells grown as neurospheres from hippocampi of Wwox KO and WT mice thus identifying 283 genes significantly dysregulated in their expression. Functional annotation of transcriptome profiling differences identified ?neurological disease? and ?CNS development related functions? to be significantly enriched. Several epilepsy-related genes were found differentially expressed in Wwox KO neurospheres. This study provides the first genotype-phenotype observations as well as potential mechanistic clues associated with Wwox loss of function in the brain.